Modelos de recuperação na mata ciliar do Rio Jaguaribe, João Pessoa, PB: análise comparativa - Freitas, Gisele Bezerra de (2011)
The riparian forests are floristic very heterogenic, as a result of the interactions of biological and physical aspects. This research was planned to survey plant species from the riparian forest of the Jaguaribe River, which is placed in the city of João Pessoa, and also to indicate their ecological groups, making possible preservation actions, management and recuperation of this specific and other similar areas. To achieve this purpose, collections of botanic material were made according to the usual techniques of taxonomy. 99 species, 88 genus and 44 botanic families of angiosperms were identified. The paper lists the species with the indication of its ecological group, state of regeneration, as well as location maps.